2012
DOI: 10.1186/1471-2261-12-87
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for pacemaker requirement after transcatheter aortic valve implantation

Abstract: BackgroundTranscatheter aortic valve implantation (TAVI) has been established as a treatment option for inoperable patients with symptomatic aortic valve stenosis. However, patients suffer frequently from conduction disturbances after TAVI.MethodsBaseline, procedural as well as surface and intracardiac ECG parameters were evaluated for patients treated with TAVI and a comparison between patients requiring pacemaker with those not suffering from relevant conduction disorders were done.ResultsTAVI was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 25 publications
3
23
0
2
Order By: Relevance
“…Akin et al. also found that a PR interval longer than 200 ms post‐TAVI was a predictive factor for the development of high degree AV block during follow‐up . These data suggest the potential importance of the PR interval as a predictor of pacemaker use.…”
Section: Discussionsupporting
confidence: 90%
“…Akin et al. also found that a PR interval longer than 200 ms post‐TAVI was a predictive factor for the development of high degree AV block during follow‐up . These data suggest the potential importance of the PR interval as a predictor of pacemaker use.…”
Section: Discussionsupporting
confidence: 90%
“…Left ventricular ejection fraction (LVEF) was in general preserved, except for 3 studies in which mean LVEF was mildly compromised (range of mean LVEF 47% to 60%). 26,27,32 The most important baseline characteristics are reported in Table 1. 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 610 611 612 613 614 615 616 617 618 619 620 621 622 623 624 625 626 627 628 629 630 631 632 633 634 635 636 637 638 639 640 641 642 643 644 645 646 647 648 649 650 651 652 653 654 655 656 657 658 659 660 A small majority of patients were treated by the transfemoral approach (51.1%), followed by the transapical approach (33.7%), and only few patients received a direct aortic or trans-subclavian procedure (1.5% and 0.2%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] It is one of the most common complications of this procedure. LBBB is a marker of poor prognosis, with an increased risk of complete atrioventricular (AV) block, heart failure and sudden cardiac death.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%